Variegated Capitalism, Chinese Style: Regional Models, Multi-scalar Constructions. Issue 1 (2nd January 2016) - Zhang, Jun; Peck, Jamie
Abstract : Zhang J. and Peck J. Variegated capitalism, Chinese style: regional models, multi-scalar constructions, Regional Studies . The paper explores tensions between the varieties of capitalism framework and the heterogeneous particularities of the Chinese case. Rather than forcing the Chinese model into analytical boxes derived, primarily, from analyses of European and North American capitalism, this complex formation more appropriately can be understood to exist in a 'triangular' relationship with the two conventional poles of varieties scholarship, the US-style 'liberal market' economy and the German-style 'coordinated market' economy. Furthermore, the substantial degree of internal (regional) heterogeneity evident in the Chinese case calls into question those models of capitalism that focus narrowly on institutional coherence at the national scale. Illustrating this point, a range of 'sub-models' of Chinese capitalism is examined: regional styles of capitalist development that remain distinct from one another, and deeply networked into a range of global production networks, and 'offshore' economies, just as they remain, to some degree, distinctively Chinese.